Anticancer Dose Adjustment for Patients with Renal and Hepatic Dysfunction: From Scientific Evidence to Clinical Application - Tomi Hendrayana; André Wilmer; Verena Kurth; Ingo GH Schmidt-Wolf; Ulrich Jaehde (MDPI AG, 2017)
Most anticancer agents exhibit a narrow therapeutic index, i.e., a small change in plasma concentrations can lead to a less efficacious treatment or an unacceptable degree of toxicity. This study aimed at providing health professionals with a feasible and time-saving tool to adapt the dose of anticancer agents for patients with renal or hepatic dysfunction. A guideline for anticancer agents was developed based on a literature search. An algorithm was generated to enhance the efficiency of the dose adaptation process. Finally, the dosing guideline was converted into an easy-to-use ExcelTM tool. The concept was applied to a total of 105 adult patients at the Centre for Integrated Oncology, Bonn, Germany. In total, 392 recommendations for dose adaptation were made and 320 (81.6%) recommendations were responded to by the oncologists. 98.4% of the recommendations were accepted. The algorithm simplifies the decision and screening process for high-risk patients. Moreover, it provides the possibility to quickly decide which laboratory tests are required and whether a dose adjustment for a particular anticancer drug is needed. The ExcelTM tool provides a recommended individual dose for patients with renal or hepatic dysfunction. The effectiveness of this strategy to reduce toxicity should be investigated in further studies before being adopted for routine use.